Home after fascism: Italian and German Jews after the Holocaust - Koch, Anna (The Modern Jewish Experience Series, 2023)
"Home after Fascism draws on a rich array of memoirs, interviews, correspondence, and archival research to tell the stories of Italian and German Jews who returned to their home countries after the Holocaust. The book reveals Jews' complex and often changing feelings toward their former homes and highlights the ways in which three distinct national contexts-East German, West German, and Italian-shaped their answers to the question, is this home? Returning Italian and German Jews renegotiated their place in national communities that had targeted them for persecution and extermination. While most Italian Jews remained deeply attached to their home country, German Jews struggled to feel at home in the "country of murderers." Yet, some retained a sense of belonging through German culture and language or felt attached to a specific region or city. Still others looked to the future; socialist and communists of Jewish origin hoped to build a better Germany in the Soviet Occupied Zone. In all three postwar states, surviving Jews fought against persistent antisemitism, faced the challenge of recovering lost homes and possessions, struggled to make sense of their persecution, and tried to find ways to reclaim a sense of belonging. Wide ranging and moving, Home after Fascism enriches our understanding of Jews' homecoming experiences after 1945. It reveals the deep affection and persistent love people feel for their homes, the suffering that comes with losing them, and the challenges of a return"--